In Situ Creep Behavior Characterization of Single Crystal Superalloy by UV-DIC at 980 °C - Yong Shang (Coatings, 2019)
High temperature creep resistance is a critical characteristic of Ni-based single crystal (SX) superalloys. In this work, the creep behavior of a Ni-based SX superalloy was in situ characterized at 980 °C by ultraviolet (UV) imaging combined two-dimensional digital image correlation (DIC) in vacuum environment. The surface pattern was fabricated to maintain stable over 65 h at 980 °C. The pattern images captured by UV imaging were analyzed using mean gray value and the full-field strain map of creep deformation was obtained. A laser displacement senor (LDS) was employed for measuring the creep strain on the specimen for comparison. The creep deformation result shows a good agreement between DIC and LDS, the microstructure of the different creep areas on the specimens also demonstrate that the results of DIC are reliable. The in situ creep characterization by UV-DIC shows a great potential for investigating creep behaviors at high temperatures.